2017
DOI: 10.1186/s12885-017-3837-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross sectional study of serum selenium concentration and esophageal squamous dysplasia in western Kenya

Abstract: BackgroundLow serum selenium status has been associated with increased risk of esophageal squamous cell carcinoma (ESCC). East Africa is a region of high ESCC incidence and is known to have low soil selenium levels, but this association has not previously been evaluated. In this study we assessed the association of serum selenium concentration and the prevalence of esophageal squamous dysplasia (ESD), the precursor lesion of ESCC, in a cross-sectional study of subjects from Bomet, Kenya.Methods294 asymptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Of the 37 studies on risk factors for EC, 18 (48.6%) were conducted in South Africa[10,70-86], 5 (13.5%) in Kenya[11,13,87-89], 3 (8.1%) in Uganda[4,5,90], 2 each in Ghana (5.4%)[7,91], Zambia (5.4%)[3,92] and Zimbabwe (5.4%)[93,94], and 1 each in Malawi (2.7%)[95], Ethiopia (2.7%)[12], Tanzania (2.7%)[6], Egypt (2.7%)[96] and Nigeria (2.7%)[97].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 37 studies on risk factors for EC, 18 (48.6%) were conducted in South Africa[10,70-86], 5 (13.5%) in Kenya[11,13,87-89], 3 (8.1%) in Uganda[4,5,90], 2 each in Ghana (5.4%)[7,91], Zambia (5.4%)[3,92] and Zimbabwe (5.4%)[93,94], and 1 each in Malawi (2.7%)[95], Ethiopia (2.7%)[12], Tanzania (2.7%)[6], Egypt (2.7%)[96] and Nigeria (2.7%)[97].…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that Se deficiency may play a role in the development of EC[74]. In a cross-sectional study in Western Kenya, Pritchet et al[89] found a high serum Se associated with prevalence of esophageal squamous dysplasia. (Q4 vs Q1: OR 3.03, 95%CI: 1.05-8.74), after adjusting for potential confounders (Q4 vs Q1: OR: 3.87, 95%CI: 1.06-14.19).…”
Section: Resultsmentioning
confidence: 99%
“…In southeastern Iran, serum selenium level was significantly lower in cancer patients than in healthy individuals (111). Furthermore, there was a significant positive correlation between serum selenium level and occurrence of esophageal squamous dysplasia in East Africa, a high-risk area for incidence of ESCC (112).…”
Section: Selenium and Antioxidant Defense Systemsmentioning
confidence: 89%
“…Cadmium and arsenic were found to be synergistically associated with bladder cancer and both exposures are often also associated with smoking status Feki-Tounsi et al, 2013b;Feki-Tounsi et al, 2014). A higher serum selenium concentration and a deficiency of zinc and molybdenum was found to be associated with esophageal squamous dysplasia (Ray et al, 2012;Pritchett et al, 2017). A positive association between cadmium exposure and pediatric cancer may also be present (Sherief et al, 2015).…”
Section: Health Outcomesmentioning
confidence: 99%